One-way tickets eaudiobook - Grainger, Peter (A Case For Willows and Lane, 2018)
When a local man, a veteran of the war in Afghanistan, goes missing, his parents have good reason to be concerned. Emily Willows is a friend of the family and says that she knows just the person to find him—and, as Summer Lane soon points out, the fact that this also fits in with Emily's plan to set up her very own detective agency is surely just a fortuitous coincidence. But it isn't long before the former detective inspector finds herself on a train heading back to London, and back into situations that she thought she had left behind. Some old acquaintances are renewed and some difficult memories must be confronted as Lane searches for the missing soldier and discovers the shocking truth about what happened to him five years earlier.